HUBUNGAN IKLIM KERJA DENGAN KOMITMEN ORGANISASI SUATU STUDI EVALUASI KINERJA KARYAWAN ( Kasus Karyawan PT. Telkom Pekanbaru) - Rena Okti Rayna; Seno Andri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
Conducive working climate is important in determining the performance of employees.High or absence of organizational commitment in self- employees are also caused by the working climate in the company.If the employment is climate conducive companies can make employees comfortable, and ultimately the commitment of employees in the company formed to even increased. And so the goal can be achieved with good company . The purpose of this research study is to know how existing work on climate PT. TELKOM Pekanbaru, to know how commitment the organization to the staff of PT. TELKOM Pekanbaru and to determine the relationship of working climate and organizational commitment staff of PT. TELKOM Pekanbaru. In analyzing this study used a statistical technique and model used in this study is the Product Moment Correlation .Based on the results of the questionnaire data processing obtained results show that there is a strong relationship between working climate and organizational commitment on the staff of PT.TELKOM Pekanbaru, where the calculation results obtained from the correlation coefficient of 0,699 and hypotheses obtained by calculating t table value of 1,995 with df : 69, and α = 0.05, and t value of 8,1225 . Thus H0 is rejected and Ha is accepted , this means working climate has a significant relationship with organizational commitment on staff of PT . TELKOM Pekanbaru.Thus it can be seen that the working climate has sizable relations with the organization's commitment to the staff of PT. TELKOM Pekanbaru. Keywords : Working Climate , Organizational Commitment